The Competition of the Insurance Company in Medan City is Undermined by the Quality of the Agent's Work - Bastanta Sinulingga; Nurul Jannah; Ahmad Muhaisin B. Syarbaini (Newinera Publisher, 2024)
The purpose of this research is to determine factors that determine competitiveness of PT. AJS Bumiputera Medan in relation to the insurance market in Medan with an emphasis of SOPs and convergence between products and services. In the present study, the research adopted a descriptive qualitative research method of data collection that entailed conducting a series of interviews with in-formants to understand the efficacy of SOPs and service strategies. The study also established that operational Standard Operating Procedures (SOPs) are crucial for continual service delivery and keep service contracts regular, but adherence forces organizations to stay rigid in executing processes, thus lacking sufficient strategic maneuverability space to overcome the variety of issues and capture the variety of demands in clients’ growing markets. The paper discusses the degree of standardisation of services and the role of ‘vehicle’ of service encounters, in relation to the flexibility of SOPs to respond to clients’ needs. Besides, the study focuses on the importance of communication in linking product lines with services offered in the organization. One of the external factors is the agent’s capacity to effectively explain the value and the benefits of the insurance products, more especially in relation to the client’s financial status; this is deemed critical in enhancing the exploitation of the market and enhancing the client’s retention especially in a world that is earmarked by economic insecurity.